Effect of grapevine genotype and environment on grape berry composition : metabolism and metabolome studies in Alvarinho, Arinto and Padeiro de Basto varieties from North and South of Portugal - Teixeira, António da Costa (2013)
Dissertação de mestrado em Biologia Molecular, Biotecnologia e Bioempreendedorismo em Plantas